Farm commercialization in Myanmar: A transformation on hold or in reverse? - Myanmar Agriculture Policy Support Activity (International Food Policy Research Institute, 2022)
Over the last decade, farms in Myanmar have gone through important market transitions. On the input side, imports of chemical fertilizer increased four-fold and agro-chemicals eight-fold while 55 percent more farmers were using mechanization rental services between 2011 and 2020. On the output side, three-quarters of Myanmar’s crop production is sold, indicating high market orientation, especially so for non-paddy crops. However, farm commercialization in Myanmar started from a low base and is still lagging peer countries in the region. The twin crises in 2020 and 2021 (the covid-19 and the political crisis) and international market developments have further led to increasing worries for an agricultural market transformation on hold or in reverse, as seen by a decline in imports of modern inputs, driven by price increases of inputs, currency policy changes, insecurity, and reduced profitability for most crop farmers. To improve farm commercialization and to catch up with peers, a better and secure business environment, openness to trade, further diversification, and improved infrastructure is called for.